Mesenchymal stem cell therapy as a game-changer in liver diseases: review of current clinical trials - Wei-Chen Huang; Yuan-Chi Li; Pin-Xuan Chen; Kevin Sheng-Kai Ma; Li-Tzu Wang (Stem Cell Research & Therapy)
Summary Chronic liver diseases, including cirrhosis and liver failure, remain formidable challenges due to their complex progression and limited therapeutic options. Mesenchymal stem cell (MSC) therapy has emerged as a game-changing approach, leveraging its potent immunomodulatory, anti-fibrotic, and regenerative capabilities, along with the ability to transdifferentiate into hepatocytes. This review delves into the latest advances in MSC-based treatments for chronic and end-stage liver diseases, as highlighted in current clinical trials. MSCs derived from bone marrow and umbilical cord have shown remarkable promise in reversing liver damage, improving liver function, and providing hope for patients who do not respond to conventional therapies. When administered through hepatic, portal, or peripheral veins, MSCs have significantly improved liver histology, reduced fibrosis, and restored functional capacity. Furthermore, MSC-derived materials, such as extracellular vesicles and exosomes, are emerging as cutting-edge tools for treating liver failure and mitigating post-transplant complications. While autologous MSC-derived hepatocytes hold promise for non-fatal cirrhosis, allogeneic MSCs are being applied in more severe conditions, including liver failure and transplantation cases. Despite these promising early outcomes, larger trials and long-term studies are essential to fully harness MSCs as a transformative, off-the-shelf alternative to liver transplantation, heralding a new era in regenerative liver therapies.